Meningkatkan Keterampilan Berpikir Kritis Menggunakan Kombinasi Model Problem Based Learning (PBL), Student Team Achievement Division Dan Talking Stick Pada Muatan Bahasa Indonesia - Bukhari; Novitawati (CV. ITTC INDONESIA, 2024)
The problem studied was the low ability of students in critical thinking. To overcome this, a combination learning model of Problem Based Learning (PBL), Student Teams Achievement Division (STAD), and Talking Stick was used. In this study using a classroom action research method (PTK) for 4 meetings, with the subject of SDN Handil Bakti class IV students in the 2023/2024 school year with a total of 30 people. Qualitative data were obtained through observation of educator and learner activities and critical thinking skills, while quantitative data were obtained from individual written tests for learner learning outcomes. The results showed that the activity of educators increased from 64% to 96% with the criteria of “Very Good”, while the activity of students increased from 47% to 93% with the criteria of “Very Active”. Critical thinking skills also increased from 37% to 87% with the criteria “Very Skilled”. While the learning outcomes of students increased from 53% to 90%. Thus, the conclusion is that the application of learning using a combination of PBL, STAD, and Talking Stick models is effective in improving students' activities, critical thinking skills, and learning outcomes.